The Influence of Organizational Culture, Work Environment, and Competence on Safety Health Occupation (SHO) Laboratory Employees with Safety Behavior as a Mediation Variable - Hermanto, Bambang; Syahrul, Laura; Yulihasri, Yulihasri (Journal of Social Research, 2023)
This study aims to know the influence of culture organization, environment work, and competence on Safety Health Occupation (SHO) employees in the laboratory with safety behavior as variable mediation. Sample from study This is a whole-employee laboratory with as many as 60 employees. Study This uses analysis descriptive and analysis inferential using the computer program SmartPLS 4.0. In addition, hypothesis testing and effect testing was carried out in mediation. Research results show that organizational culture and work environment have a positive and insignificant effect on Safety Health Occupation, competence has a positive and significant effect on Occupational Safety and Health, organizational culture has a positive and insignificant effect on safety behavior, Work Environment, and competence Has a Positive and Significant Influence on Safety Behavior, safety Behavior has a positive and significant effect on Safety Health Occupation, safety Behavior cannot mediate the Influence of Organizational Culture on Occupational Safety and Health (SHO) of Laboratory Employees, Safety Behavior Can Mediate the Influence of the Work Environment on Occupational Safety and Health (SHO) of Laboratory Employees, and safety behavior can mediate the influence of competence on Safety Health Occupation (SHO) of Laboratory Employees.